The Experiences of Handling Postpartum Hemorrhage According To Various Perspectives: A Scoping Review - Indah Christiana; Sulistyaningsih Sulistyaningsih (Universitas Aisyah Pringsewu, 2023)
One leading cause of maternal mortality and morbidity is postpartum hemorrhage (PPH). When postpartum hemorrhage is not appropriately treated, shock and loss of consciousness can occur due to a large amount of blood coming out. It causes impaired blood circulation throughout the body and can cause severe hypovolemia. If this happens, it could result in the mother not being saved. Reducing deaths from postpartum hemorrhage is a challenge that must be undertaken by mothers, families or partners, service providers, and health workers. Research Objectives: to review research results from the experience of postpartum hemorrhage management according to various perspectives. The scope of this review uses the PRISMA ScR framework with article searches using four databases, namely Pubmed, ScienceDirect, Wiley, and EBSCO. The data obtained was carried out Critical Appraisal Using The Joanna Briggs Institute (JBI). Based on the search for articles from the 3,032 that had been selected, eight articles met the inclusion criteria. This review found three main themes: knowledge of postpartum haemorrhage (PPH) and prevention and treatment of PPH. Early detection of at-risk women, regular ANC, empowering women and villagers, the importance of seeing a midwife at least once while pregnant, carrying out treatment, and referrals are important so that postpartum hemorrhage is handled immediately. Abstrak: Perdarahan postpartum merupakan penyebab utama kematian dan kesakitan ibu. Perdarahan post partum yang tidak tertangani dengan baik dapat mengakibatkan syok dan menurunnya kesadaran, akibat banyaknya darah yang keluar. Hal ini menyebabkan gangguan sirkulasi darah ke seluruh tubuh dan dapat menyebabkan hipovolemia berat. Bila hal ini terjadi bisa mengakibatkan ibu tidak terselamatkan. Mengurangi kematian akibat perdarahan postpartum merupakan tantangan yang harus dilakukan baik ibu, keluarga atau pasangan, penyedia layanan dan tenaga kesehatan. Tujuan Penelitian: untuk mereview hasil penelitian dari pengalaman penanganan perdarahan postpartum menurut berbagai perspektif. Scoping review ini menggunakan framework PRISMA ScR dengan pencarian artikel menggunakan 4 database yaitu Pubmed, ScienceDirect, Wiley dan EBSCO. Data yang sudah didapatkan dilakukan Critical Apraisal Menggunakan The Joanna Briggs Institute (JBI). Berdasarkan pencarian artikel dari 3.032 yang telah diseleksi didapatkan sebanyak 8 artikel yang sesuai dengan kriteria inklusi. Dalam tinjauan ini ditemukan tiga tema utama yaitu pengetahuan perdarahan, pencegahan dan penanganan perdarahan postpartum. Penanganan perdarahan postpartum dilakukan mulai deteksi dini wanita beresiko, ANC secara teratur, melakukan pemberdayaan perempuan dan penduduk desa, pentingnya menemui bidan setidaknya sekali selama kehamilan, melakukan pengobatan serta rujukan.